ChemInform Abstract: Broensted Acid‐Catalyzed Intramolecular Nucleophilic Substitution of the Hydroxyl Group in Stereogenic Alcohols with Chirality Transfer. Issue 38 (3rd September 2015) - Bunrit, Anon; Dahlstrand, Christian; Olsson, Sandra K.; Srifa, Pemikar; Huang, Genping; Orthaber, Andreas; Sjoeberg, Per J. R.; Biswas, Srijit; Himo, Fahmi; Samec, Joseph S. M.
Abstract The H3PO2‐catalyzed cyclization of enantioenriched γ‐nucleophile functionalized alcohols to saturated 5‐membered O‐, S‐, and N‐heterocycles is presented.